Extreme weather events in Poland in the 21st century - Jacek Tylkowski (Kazimierz Wielki University, 2017)
This papers presents the temporal and spatial variation in the occurrence of extreme weather events in Poland which are not recorded by the Institute of Meteorology and Water Management at its meteorological stations. On the grounds of the European Severe Weather Database, the study covered the occurrence of weather geo-threats such as: avalanche, dust devil, funnel cloud, gustnado, large hail, ice accumulation, damaging lightning, heavy rain, heavy, snowfall, tornado, severe wind within 2000-2016. The study also includes a case study on the extreme weather event called a bow echo which took place on 12 August 2017 and caused fatalities and significant economic losses within 6 voivodeships.